Microstructures and properties of graphite and Al2O3 short fibers reinforced Mg-Al-Zn alloy hybrid composites - 杨晓红 刘勇兵 宋起飞 安健 (Transactions of Nonferrous Metals Society of China, 2006)
Graphite and Al2O3 short fibers reinforced Mg-Al-Zn alloy hybrid composites were fabricated by perform squeeze-infiltration route. The effects of the volume of graphite particles on the microstructure, mechanical properties and tr/bological behavior were investigated under the conditions of constant size of graphite particle and volume of Al2O3 short fiber. The results reveal that the uniform distribution of the reinforced graphite particles and Al2O3 short fiber can be obtained by this technique, and they have strong bonding with the metal matrix. Increasing graphite volume results in decrease in hardness, the ultimate tensile strength whereas the Al2O3 short fiber makes contribution to the increase in hardness of the composite. The composite exhibits good wear resistance, small wear mass loss and low coefficient of friction as compared with the metal matrix. The wear mechanisms transit from oxidation wear, abrasion wear into delamination wear as the applied load is increased, and a film of lubricant covering almost entire surface of specimen, is found to be formed, which separates the wear surfaces from metal to metal contact and thus improves the tribological properties.